1994
DOI: 10.1111/j.1527-3466.1994.tb00289.x
|View full text |Cite
|
Sign up to set email alerts
|

TCV‐116: A New Angiotensin II Type‐1 Receptor Antagonist

Abstract: Key Words: Angiotensin I1 type-1 receptor antagonist--CV-1 1974-hypertension-TCV-1 16The renin-angiotensin system plays an important role in the development and maintenance of hypertension, and in recent years, attempts have been made to treat hypertension by suppressing the renin-angiotensin system (2). Because of their established antihypertensive effect, inhibitors of angiotensin converting enzyme (ACE) are now widely used in patients with hypertension and congestive cardiac failure. However, ACE inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…42 Preclinical studies suggest that candesartan cilexetil has a cardioprotective effect and is also effective in the prevention and regression of left ventricular hypertrophy (LVH). 10,11 The effect of candesartan cilexetil on regression of LVH has been confirmed in short-term clinical trials. Echocardiography and cine-MRI examination show that treatment with 2-12 mg of candesartan cilexetil once daily for 12 to 24 weeks reduced left ventricular weight by 7.7% to 9.3% in patients with mild to moderate essential hypertension.…”
Section: Target Organ Protection With Candesartan Cilexetilmentioning
confidence: 78%
See 1 more Smart Citation
“…42 Preclinical studies suggest that candesartan cilexetil has a cardioprotective effect and is also effective in the prevention and regression of left ventricular hypertrophy (LVH). 10,11 The effect of candesartan cilexetil on regression of LVH has been confirmed in short-term clinical trials. Echocardiography and cine-MRI examination show that treatment with 2-12 mg of candesartan cilexetil once daily for 12 to 24 weeks reduced left ventricular weight by 7.7% to 9.3% in patients with mild to moderate essential hypertension.…”
Section: Target Organ Protection With Candesartan Cilexetilmentioning
confidence: 78%
“…9 Preclinical experiments have revealed that candesartan cilexetil has potent and long-lasting hypotensive effects in spontaneously hypertensive, as well as in renal hypertensive, rats. 10 Prevention of hypertensive organ damage was confirmed in the brain, heart, and kidney of spontaneously hypertensive, stroke-prone (SHR-SP) and DOCA-salt rats, and candesartan cilexetil caused regression of cardiac hypertrophy without deterioration of cardiac function in spontaneously hypertensive and SHR-SP rats. 11,12 In previous preliminary clinical studies we confirmed that candesartan cilexetil has a potent, longlasting angiotensin-antagonistic and antihypertensive action in normal volunteers and in patients with essential hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…The AUC of candesartan is not significantly affected by food intake. 28,106 T max is reached 3-5 h after oral administration. Serum concentrations (AUC) displayed dose linearity with increasing doses in the therapeutic dose range.…”
Section: Candesartan-cilexetil/candesartanmentioning
confidence: 98%
“…28,106 Candesartan is mainly eliminated unchanged via urine and bile, and is only to a minor extent inactivated by hepatic metabolism. So far, only one inactive metabolite (CV15959) has been described.…”
Section: Candesartan-cilexetil/candesartanmentioning
confidence: 99%
“…TCV-116 is a prodrug, and only its metabolite, CV-I 1974, has significant biological activity (22,29). A review of TCV-I 16 has already been published in this journal (25). …”
Section: Introductionmentioning
confidence: 99%